Natural coagulant from cassava peel (Manihot esculenta) for domestic wastewater (Research, Society and Development, 2025)
This study aims to evaluate the use of a biocoagulant derived from cassava peel (Manihot esculenta) to improve the quality of domestic wastewater, comparing it with ferric chloride (FeCl₃) as a chemical coagulant. Water samples were collected from an oxidation lagoon in Calceta, Ecuador, and several water quality parameters were analyzed. The results showed that FeCl₃ is effective in the removal of total solids (TS) and turbidity, while the biocoagulant excelled in reducing total suspended solids (TSS). The combination of coagulants proved to be the most effective option, standing out in the turbidity removal, and color, with a reduced impact on pH and electrical conductivity, making it a more sustainable treatment. Statistical analyses, including ANOVA and Tukey HSD, revealed significant differences between the coagulant doses, with the combination of FeCl₃ and the biocoagulant showing the best results. These findings support the combined chemical and natural coagulants used to improve the water quality treated while minimizing environmental impact. However, further research is needed to optimize these treatments and ensure their feasibility on a larger scale.